Fluorocarbon anticorrosive paint and preparation method thereof
By cross-linking and curing with fluorocarbon modified hydroxyacrylic resin, graphene and melamine compounds in aqueous fluorocarbon anticorrosion coatings, and adding functional additives of modified carbon nanotubes and aluminum powder, the problem of insufficient weather resistance of aqueous fluorocarbon anticorrosion coatings is solved, and the high weather resistance and corrosion resistance of the coating are achieved.
Patent Information
- Application Number
- CN202510016376.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
Water-based fluorocarbon anticorrosion coatings do not perform well in weather resistance, and are prone to pore shrinkage and long drying time, which affects the uniformity and corrosion resistance of the coating.
Fluorocarbon modified hydroxyacrylic resin, graphene and melamine compounds are cross-linked and cured to form a coating, and functional additives of modified carbon nanotubes and aluminum powder are added to improve the weather resistance of the coating through compounding and synergistic effects.
It significantly improves the corrosion resistance and weather resistance of the coating, prevents the penetration of corrosive media, extends the service life of the coating, and improves the hydrophobicity and chemical corrosion resistance of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of water-based coatings, and more specifically, to a fluorocarbon anti-corrosion coating and a preparation method thereof. Background Art
[0002] Fluorocarbon coatings have very strong anti-corrosion properties. As a topcoat for heavy-duty anti-corrosion coatings, fluorocarbon paints can be used for ships, port facilities, bridges, steel structures, oil drilling platforms, storage facilities, and chemical equipment for outdoor anti-corrosion, as well as for exterior decoration of engineering vehicles and equipment. At the same time, water-based paints, as one of the types of environmentally friendly products regulated by the state, have become the protagonist of the current coatings market with their absolute advantages such as low VOC content, no strong irritating odor, and environmental friendliness. Water-based fluorocarbon paints came into being in this environment.
[0003] Water-based fluorocarbon paint uses water-based fluorocarbon emulsion as film-forming material. It is a highly weather-resistant protective coating with high film hardness, good stain resistance, and low VOC content. It is more environmentally friendly than oil-based fluorocarbon paint and is also an environmentally friendly and healthy coating. Water-based fluorocarbon paint is a water-based coating. Its main components include resin, pigment, filler, additives, etc. Among them, resin is one of the main components of water-based fluorocarbon paint, which determines the weather resistance, chemical resistance, adhesion, etc. of water-based fluorocarbon paint. Common water-based fluorocarbon paint resins include polyurethane resin, acrylic resin, epoxy resin, phenolic resin, etc.; pigment is a coloring component in water-based fluorocarbon paint, which can meet the different needs of customers through different colors; filler mainly plays the role of filling and increasing the thickness of the coating film; additives can adjust the rheology, consistency, drying time, etc. of the coating.
[0004] However, water-based fluorocarbon paint technology has only begun to develop in recent years, and the product is not yet particularly mature. Since the surface tension of water is higher than that of organic solvents, it has poor wettability on the coated substrate and is prone to shrinkage, which affects the uniformity of the coating. In addition, the drying of water-based paint requires more energy and longer time, which may cause the coating to be more affected by the external environment during the drying process. Therefore, water-based fluorocarbon anti-corrosion coatings perform worse than oil-based fluorocarbon anti-corrosion coatings in terms of weather resistance, and still needs to be improved. Summary of the invention
[0005] In order to improve the weather resistance of water-based fluorocarbon anti-corrosion coatings, the present application provides a fluorocarbon anti-corrosion coating and a preparation method thereof.
[0006] In the first aspect, the present application provides a fluorocarbon anti-corrosion coating, which adopts the following technical solution: A fluorocarbon anticorrosive coating comprises a component A and a component B which are stored separately and mixed when used, and the component A comprises the following raw materials in parts by weight: 35-56 parts of fluorocarbon modified hydroxy acrylic resin; 10-15 parts water; Graphene powder 0.1-0.5 parts; Pigment 15-25 parts; 1-2 parts of fluorinated surfactant; The B component comprises the following raw materials in parts by weight: 10-12 parts of melamine compounds; The fluorocarbon-modified hydroxy acrylic resin is prepared by the following steps: Add ethylene glycol butyl ether into a reaction container, add an initiator and a monomer mixture dropwise after heating, keep warm and stir to react after the addition is completed, and add deionized water and a neutralizer to obtain a fluorocarbon-modified hydroxy acrylic resin; The monomer mixture is composed of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic acid monomer and hydroxyethyl methacrylate monomer in a weight ratio of (1-2):1:(2-5):(3-6).
[0007] By adopting the above technical scheme, graphene has excellent anti-corrosion performance. The coating formed by cross-linking and curing fluorocarbon-modified hydroxy acrylic resin, graphene and melamine compounds can effectively hinder the penetration of corrosive media, effectively improve the anti-corrosion performance of the coating, and the coating has ultra-low surface energy and hydrophobicity, so that acid rain, condensation or other corrosive media cannot stay on the surface of the coating, and can further prevent the corrosive media from penetrating into the interior of the coated substrate, thereby bringing a relatively excellent anti-corrosion effect. At the same time, the fluorocarbon-modified hydroxy acrylic resin is prepared by free radical copolymerization with butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and hydroxyethyl methacrylate monomer as a monomer mixture, and the butyl acrylate monomer can help form a strong chemical bond and improve flexibility, adhesion and durability; the methacrylic acid monomer can provide the resin with better adhesion and wettability of pigments and fillers, has high activity in the polymerization reaction, can be copolymerized with other monomers or functional groups, and exerts the excellent characteristics of various different monomers; the fluorine-containing acrylic monomer contains fluorine atoms, which makes it relatively chemically inert and high Temperature stability, after copolymerizing with other monomers to form a polymer, it can exhibit excellent chemical corrosion resistance, high temperature resistance and low friction coefficient and other characteristics; the molecular structure of the hydroxyethyl methacrylate monomer contains hydroxyl and acrylic double bonds, which can provide more cross-linking points in the polymerization reaction, thereby enhancing the mechanical properties and chemical stability of the polymer; and the butyl acrylate monomer, methacrylate monomer, fluorine-containing acrylic monomer and hydroxyethyl methacrylate monomer cooperate with each other to copolymerize to obtain fluorocarbon-modified hydroxy acrylic resin, which can show relatively excellent weather resistance, thereby significantly improving the service life of the fluorocarbon anti-corrosion coating during the application process.
[0008] Preferably, the monomer mixture is composed of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic acid monomer and hydroxyethyl methacrylate monomer in a weight ratio of 1.5:1:3:5.
[0009] By adopting the above technical scheme, when a monomer mixture consisting of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and hydroxyethyl methacrylate monomer in the above weight ratio is used, the polymer chains with relatively uniform and stable structures formed by mutual polymerization have better coordination effect with each other, so that the obtained fluorocarbon-modified hydroxy acrylic resin can be fully combined with other component raw materials after application and stably exert its own effects, and finally a fluorocarbon anti-corrosion coating with excellent weather resistance is obtained.
[0010] Preferably, the fluorine-containing acrylic monomer is one or a combination of hexafluorobutyl acrylate, trifluoroethyl methacrylate, perfluorohexylethyl acrylate, dodecafluoroheptyl methacrylate and perfluorooctylethyl methacrylate.
[0011] By adopting the above technical scheme, the above types of fluorine-containing acrylic monomers can exert an excellent and stable coordination mechanism with butyl acrylate monomers, methacrylic acid monomers, and methacrylic acid monomers, and can better protect the fluorocarbon-modified hydroxy acrylic resin from the influence of the external environment, and can maintain good performance in various harsh environments, thereby enabling the fluorocarbon anti-corrosion coating to exert excellent and stable weather resistance.
[0012] Preferably, 1-3 parts by weight of a functional additive are further added to the raw materials of component A, wherein the functional additive is composed of modified carbon nanotubes and aluminum powder in a weight ratio of (5-9):1, and the modified carbon nanotubes are prepared by the following steps: adding the carbon nanotube raw material to a mixed acid solution of nitric acid and sulfuric acid, ultrasonically treating at 40-50°C for 6-8h, then cooling and standing for a period of time, diluting, filtering and washing with water to neutralize, and then vacuum drying to obtain the obtained product.
[0013] By adopting the above technical solution, carbon nanotubes have extremely high strength and elastic modulus, and thermal stability. This enhancement effect enables the coating to better maintain its integrity and protective effect in harsh environments; and the modified carbon nanotubes obtained by modifying the carbon nanotubes can be fully wrapped by the fluorocarbon modified hydroxy acrylic resin, thereby being able to play an excellent role in enhancing weather resistance. Aluminum powder can significantly enhance the weather resistance of the coating, resist the corrosion of the coating by external environments such as ultraviolet rays and oxidation, and aluminum powder can also withstand high temperature and chemical corrosion, thereby maintaining the gloss of the surface coating and its defense against external influences. At the same time, when the modified carbon nanotubes and aluminum powder are used as functional additives, the two can play an excellent compounding and synergistic role with each other, utilizing the nano effect of the modified carbon nanotubes and forming a stable interface with the aluminum powder, thereby significantly improving the weather resistance of the fluorocarbon anti-corrosion coating.
[0014] Preferably, the functional additive is composed of modified carbon nanotubes and aluminum powder in a weight ratio of 7:1.
[0015] By adopting the above technical scheme, when the modified carbon nanotubes and aluminum powder in the above weight ratio are used in combination, the coordinated effect between them is more significant. The two can form a uniformly dispersed and mutually interpenetrated reinforcement system in the mixing system of the fluorocarbon anti-corrosion paint coating, thereby making the functional additives have a more excellent improvement in the weather resistance of the fluorocarbon anti-corrosion coating.
[0016] Preferably, the carbon nanotube raw material is a multi-walled carbon nanotube with a diameter of 10-20 nm and a length of 1-10 μm; and the particle size of the aluminum powder is 25-35 μm.
[0017] By adopting the above technical solution, the modified carbon nanotubes obtained after the carbon nanotube raw materials of the above specifications are modified are not easy to agglomerate, can be evenly dispersed in the mixed system of the fluorocarbon anti-corrosion coating, and form a stable coordination effect with the aluminum powder. The smaller the particle size of the aluminum powder, the larger the surface area is generally, and the more significant the impact on the performance of the coating is, but the smaller the particle size, the more difficult it is to disperse the aluminum powder, and the aluminum powder of the above particle size can not only play an excellent and stable role itself, but also form a relatively excellent coordination system with the modified carbon nanotubes. In this way, the corresponding effects brought about by the application of functional additives can be more stably and excellently exerted, and the weather resistance quality of the fluorocarbon anti-corrosion coating is also better.
[0018] Preferably, the nitric acid is a nitric acid solution with a mass fraction of 70%, the sulfuric acid is concentrated sulfuric acid with a mass fraction of 98%, and the volume mixing ratio of the nitric acid to the sulfuric acid is 1:(3-5).
[0019] By adopting the above technical scheme, when the above mass fractions of nitric acid and sulfuric acid are mixed and used in the above volume ratio, it is possible to bring about a better modification effect on the surface of the carbon nanotube raw material, and by introducing more and more uniform functional groups on the surface of the carbon nanotube raw material, the obtained modified carbon nanotubes can exert a better effect, and when used with aluminum powder to form a functional additive, the weather resistance improvement effect brought by the fluorocarbon anti-corrosion coating is better.
[0020] Preferably, the fluorine-containing surfactant is FS-31 fluorocarbon surfactant.
[0021] By adopting the above technical solution, FS-31 fluorocarbon surfactant can reduce the surface tension of fluorocarbon anti-corrosion coatings, significantly improve the leveling and wettability of the coatings, and the fluorinated surfactants on the side chains of its polymer skeleton form a water- and oil-repellent layer on the outer layer, which can improve the salt spray resistance, corrosion and rust resistance, and UV resistance of the fluorocarbon coatings, thereby bringing about excellent weather resistance of the fluorocarbon anti-corrosion coatings.
[0022] In a second aspect, the present application provides a method for preparing a fluorocarbon anticorrosive coating, using the following technical solution: A method for preparing a fluorocarbon anticorrosive coating comprises the following steps: (1) preparing raw materials including fluorocarbon-modified hydroxy acrylic resin, water, graphene powder, pigment, fluorinated surfactant and melamine compound according to a ratio; (2) After mixing the water and the fluorine-containing surfactant in step (1), graphene powder and pigment are added, stirred and mixed, and then ground, and then fluorocarbon-modified hydroxy acrylic resin is added, stirred and mixed to obtain component A; and the melamine compound is component B; (3) When in use, component A and component B are stirred and mixed to obtain a fluorocarbon anti-corrosion coating.
[0023] By adopting the above technical scheme, the above preparation method is simple to operate, and each raw material is added and used in steps, which is conducive to quality control in the production process and enables the various component raw materials to fully cooperate with each other, thereby obtaining a fluorocarbon anti-corrosion coating with excellent quality and stable quality, which is also conducive to large-scale industrial production as a whole.
[0024] Preferably, step (2) is specifically configured as follows: after mixing the water and fluorine-containing surfactant in step (1), graphene powder and pigment are added, stirred and mixed, and then ground to a particle size of 5-40 μm, and then fluorocarbon-modified hydroxy acrylic resin is added, stirred and mixed to obtain component A; and the melamine compound is component B.
[0025] By adopting the above technical scheme, after adding graphene powder and pigment, grinding to a particle size of 5-40μm, the precipitation rate in the coating can be slow, the stability is good, and the coating thickness is uniform, so that the corresponding effects of the coordination between the various component raw materials are relatively stable and excellent, which is conducive to obtaining a fluorocarbon anti-corrosion coating with excellent weather resistance.
[0026] In summary, this application has the following beneficial effects: 1. The present application uses butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic acid monomer and hydroxyethyl methacrylate monomer as a monomer mixture, and adopts a free radical copolymerization method to synthesize a fluorocarbon-modified hydroxy acrylic resin, and then cross-links and cures the fluorocarbon-modified hydroxy acrylic resin, graphene and melamine compounds, so that the coating formed by the fluorocarbon anti-corrosion coating can show relatively excellent weather resistance; 2. The present application adds functional additives consisting of modified carbon nanotubes and aluminum powder. Through the complex synergistic effect between the two, the nano effect of the modified carbon nanotubes and the formation of a stable interface bond with the aluminum powder, a uniformly dispersed and mutually interpenetrating reinforcement system can be formed in the mixed system of the fluorocarbon anti-corrosion coating, thereby significantly improving the weather resistance of the fluorocarbon anti-corrosion coating. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0028] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available: Graphene powder was purchased from Shijiazhuang Zhenxing Building Materials Co., Ltd. White graphene powder with an average particle size (D50) of 8 μm; the pigment was titanium dioxide; Melamine compounds were purchased from Shandong Chengtai Chemical Co., Ltd. AS-88.
[0029] Preparation examples of raw materials and / or intermediates Preparation Example 1 A fluorocarbon-modified hydroxy acrylic resin is prepared by the following steps: Add ethylene glycol butyl ether into the reaction container, heat it to 120°C and then drop the initiator and monomer mixture. After 2 hours of dropwise addition, stir and react for 2 hours. After the reaction, cool it to 90°C, add deionized water and neutralizer to obtain fluorocarbon modified hydroxy acrylic resin.
[0030] Note: In the above operation, the monomer mixture is composed of butyl acrylate monomer, methacrylic acid monomer, fluorinated acrylic acid monomer and hydroxyethyl methacrylate monomer in a weight ratio of 1.5:1:3:5; the weight ratio of the monomer mixture to ethylene glycol butyl ether is 1:1.2; the initiator is tert-butyl perbenzoate, accounting for 0.2% of the weight of the monomer mixture; the neutralizer is DMAE, accounting for 2% of the weight of the monomer mixture; the weight ratio of deionized water to the monomer mixture is 3:1; the fluorinated acrylic monomer is perfluorooctyl ethyl methacrylate.
[0031] Preparation Example 2 A fluorocarbon modified hydroxy acrylic resin is different from Preparation Example 1 in that the monomer mixture consists of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and methacrylic acid monomer hydroxyethyl ester monomer in a weight ratio of 1:1:2:3.
[0032] Preparation Example 3 A fluorocarbon modified hydroxy acrylic resin is different from Preparation Example 1 in that the monomer mixture consists of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and methacrylic acid monomer hydroxyethyl ester monomer in a weight ratio of 2:1:5:6.
[0033] Preparation Example 4 A fluorocarbon modified hydroxy acrylic resin is different from Preparation Example 1 in that the monomer mixture consists of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and methacrylic acid monomer hydroxyethyl ester monomer in a weight ratio of 1.5:1:3.5:4.5.
[0034] Preparation Example 5 A fluorocarbon modified hydroxy acrylic resin is different from Preparation Example 1 in that the monomer mixture consists of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and methacrylic acid monomer hydroxyethyl ester monomer in a weight ratio of 0.9:1:1.9:2.9.
[0035] Preparation Example 6 A fluorocarbon modified hydroxy acrylic resin is different from Preparation Example 1 in that the monomer mixture consists of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and methacrylic acid monomer hydroxyethyl ester monomer in a weight ratio of 2.1:1:5.1:6.1.
[0036] Preparation Example 7 A modified carbon nanotube is prepared by the following steps: The carbon nanotube raw material is added to a mixed acid solution of nitric acid and sulfuric acid, ultrasonically treated at 40-50°C for 6-8h, then cooled to 25°C and allowed to stand for 12h, diluted, filtered and washed with water to neutralize, and then vacuum dried at 120°C for 6h.
[0037] Note: In the above operation, ultrasonic treatment was performed at 45°C for 6h; the carbon nanotube raw material was multi-walled carbon nanotubes with a diameter of 15nm and a length of 5.5μm; the nitric acid was a nitric acid solution with a mass fraction of 70%, the sulfuric acid was a concentrated sulfuric acid with a mass fraction of 98%, and the volume mixing ratio of nitric acid to sulfuric acid was 1:4.
[0038] Preparation Example 8 A modified carbon nanotube, which is different from the one in Preparation Example 7 in that the carbon nanotube raw material is a multi-walled carbon nanotube with a diameter of 10 nm and a length of 1 μm.
[0039] Preparation Example 9 A modified carbon nanotube, which is different from the one in Preparation Example 7 in that the carbon nanotube raw material is a multi-walled carbon nanotube with a diameter of 20 nm and a length of 10 μm.
[0040] Preparation Example 10 A modified carbon nanotube, which is different from Preparation Example 7 in that the nitric acid is a nitric acid solution with a mass fraction of 70%, the sulfuric acid is concentrated sulfuric acid with a mass fraction of 98%, and the volume mixing ratio of the nitric acid to the sulfuric acid is 1:3.
[0041] Preparation Example 11 A modified carbon nanotube, which is different from Preparation Example 7 in that the nitric acid is a nitric acid solution with a mass fraction of 70%, the sulfuric acid is concentrated sulfuric acid with a mass fraction of 98%, and the volume mixing ratio of the nitric acid to the sulfuric acid is 1:5. Example
[0042] Example 1 A fluorocarbon anticorrosive coating comprises a component A and a component B which are stored separately and mixed when used, and the raw materials of the component A and the component B and their corresponding weights are shown in Table 1, and the coating is prepared by the following steps: (1) preparing raw materials including fluorocarbon-modified hydroxy acrylic resin, water, graphene powder, pigment, fluorinated surfactant and melamine compound according to a ratio; (2) After mixing the water and the fluorine-containing surfactant in step (1), add the graphene powder and the pigment, stir and mix, grind to a particle size of 5-40 μm, then add the fluorocarbon-modified hydroxy acrylic resin, stir and mix to obtain component A; and the melamine compound is component B; (3) When in use, component A and component B are stirred and mixed to obtain a fluorocarbon anti-corrosion coating.
[0043] Note: In the above operation, the fluorocarbon-modified hydroxy acrylic resin is obtained from Preparation Example 1; the fluorinated surfactant is FS-31 fluorocarbon surfactant.
[0044] Example 2-3 A fluorocarbon anticorrosive coating, which is different from Example 1 in that the raw materials of component A and component B and their corresponding weights are shown in Table 1.
[0045] Table 1 Raw materials and weight portions of components A and B in Examples 1-3 (kg / portion) Example 4 A fluorocarbon anti-corrosion coating, which is different from Example 1 in that the fluorocarbon modified hydroxy acrylic resin is obtained from Preparation Example 2.
[0046] Example 5 A fluorocarbon anti-corrosion coating, which is different from Example 1 in that the fluorocarbon-modified hydroxy acrylic resin is obtained from Preparation Example 3.
[0047] Example 6 A fluorocarbon anti-corrosion coating, which is different from Example 1 in that the fluorocarbon-modified hydroxy acrylic resin is obtained from Preparation Example 4.
[0048] Example 7 A fluorocarbon anti-corrosion coating, which is different from Example 1 in that 2 parts by weight of a functional additive are also added to the raw materials of component A, the functional additive is composed of modified carbon nanotubes and aluminum powder in a weight ratio of 7:1, and the functional additive is added together with the fluorocarbon modified hydroxy acrylic resin: the particle size of the aluminum powder is 30 μm, and the modified carbon nanotubes are obtained in Preparation Example 7.
[0049] Example 8 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the weight portion of the functional additive added is 1 part.
[0050] Example 9 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the weight parts of the functional additive added is 3 parts.
[0051] Example 10 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the functional additive consists of modified carbon nanotubes and aluminum powder in a weight ratio of 5:1.
[0052] Embodiment 11 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the functional additive consists of modified carbon nanotubes and aluminum powder in a weight ratio of 9:1.
[0053] Example 12 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the modified carbon nanotubes are obtained from Preparation Example 8.
[0054] Embodiment 13 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the modified carbon nanotubes are obtained from Preparation Example 9.
[0055] Embodiment 14 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the modified carbon nanotubes are obtained from Preparation Example 10.
[0056] Embodiment 15 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the modified carbon nanotubes are obtained from Preparation Example 11.
[0057] Example 16 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the particle size of the aluminum powder is 25 μm.
[0058] Embodiment 17 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the particle size of the aluminum powder is 35 μm.
[0059] Embodiment 18 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that no aluminum powder is used in the raw materials.
[0060] Embodiment 19 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that no modified carbon nanotubes are used in the raw materials.
[0061] Embodiment 20 A fluorocarbon anti-corrosion coating, which is different from Example 7 in that the modified carbon nanotubes are replaced with unmodified carbon nanotube raw materials.
[0062] Embodiment 21 A fluorocarbon anti-corrosion coating, which is different from Example 18 in that the modified carbon nanotubes are replaced with unmodified carbon nanotube raw materials.
[0063] Comparative Example Comparative Example 1 A fluorocarbon anti-corrosion coating, which is different from Example 1 in that the fluorocarbon-modified hydroxy acrylic resin is obtained from Preparation Example 5.
[0064] Comparative Example 2 A fluorocarbon anti-corrosion coating, which is different from Example 1 in that the fluorocarbon modified hydroxy acrylic resin is obtained from Preparation Example 6.
[0065] Performance test samples: The fluorocarbon anti-corrosion coating obtained in Example 1-21 was used as test sample 1-21, and the fluorocarbon anti-corrosion coating obtained in Comparative Example 1-2 was used as control sample 1-2.
[0066] Test method: QUV weathering instrument was used to conduct the experiment. Environmental conditions were set according to GB 1865-97 "Artificial weathering and artificial radiation exposure (filtered atmospheric arc radiation) of paints and varnishes": illumination temperature 60±1℃ / 4 hours, condensation temperature 50±1℃ / 4 hours, cycle temperature 40℃, irradiance 50W / m 2 , irradiation wavelength: 300-400nm, blackboard temperature is 65℃, relative humidity is 70%, and the test period is set to 250h. A precision colorimeter is used to detect the color difference value of the fluorocarbon anticorrosive coating in its initial state and the state after the above aging. The larger the color difference value (ΔE), the worse the weather resistance of the water-based fluorocarbon anticorrosive coating. After completing the above tests on test samples 1-21 and control samples 1-2, the corresponding results are recorded in Table 2.
[0067] Table 2 Test results of test samples 1-21 and control samples 1-2 sample Color difference (ΔE) Test sample 1 0.47 Test sample 2 0.51 Test sample 3 0.50 Test sample 4 0.49 Test sample 5 0.53 Test sample 6 0.52 Test sample 7 0.12 Test sample 8 0.16 Test sample 9 0.14 Test sample 10 0.17 Test sample 11 0.15 Test sample 12 0.16 Test sample 13 0.18 Test sample 14 0.15 Test sample 15 0.19 Test sample 16 0.17 Test sample 17 0.18 Test sample 18 0.36 Test sample 19 0.33 Test sample 20 0.25 Test sample 21 0.39 Control sample 1 1.31 Control sample 2 1.42 It can be seen from Examples 1-6 and Comparative Examples 1-2 and Table 2 that by using a monomer mixture composed of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic acid monomer and hydroxyethyl methacrylate monomer in a specific weight ratio range, and synthesizing a fluorocarbon-modified hydroxy acrylic resin by a free radical copolymerization method, and then applying the fluorocarbon-modified hydroxy acrylic resin to a fluorocarbon anticorrosive coating, the coating formed by the fluorocarbon anticorrosive coating can exhibit excellent weather resistance; wherein, when the monomer mixture is composed of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic acid monomer and hydroxyethyl methacrylate monomer in a weight ratio of 1.5 :1:3:5, the corresponding effect brought by the fluorocarbon modified hydroxy acrylic resin after application is better; at the same time, when the mixing ratio of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and methacrylic acid monomer hydroxyethyl ester monomer exceeds the range of (1-2):1:(2-5):(3-6), it is found from the above test results that the color difference value (ΔE) will be significantly increased, indicating that the weather resistance of the fluorocarbon anti-corrosion coating is not good, while butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic monomer and methacrylic acid monomer hydroxyethyl ester monomer in a specific weight ratio range can bring more significant and excellent corresponding effects.
[0068] Combining Example 1 and Example 7-11 with Table 2, it can be seen that the addition of functional additives composed of modified carbon nanotubes and aluminum powder can further improve the weather resistance of fluorocarbon anti-corrosion coatings, and the color difference value (ΔE) measured by the above test will be further reduced; among them, when the modified carbon nanotubes and aluminum powder are used in a weight ratio of 7:1, the corresponding improvement effect brought about by the application of functional additives is better. Combining Example 18-19 with Table 2, it can be seen that if modified carbon nanotubes or aluminum powder are added and used alone, although the color difference value (ΔE) can be reduced, the reduction is limited, and the sum of the effects brought about by the application of the two is far less than the excellent effect brought about by the combination of the two. It can be seen that the modified carbon nanotubes and aluminum powder can bring a significant improvement effect of 1+1>2, so that the weather resistance of the fluorocarbon anti-corrosion coating is significantly improved. Combined with Examples 20-21 and Table 2, it can be seen that if the modified carbon nanotubes are replaced with unmodified carbon nanotube raw materials, it is found that the effect brought by the carbon nanotube raw materials is far inferior to that of the modified carbon nanotubes, and the carbon nanotube raw materials cannot play a compound synergistic effect when used in combination with aluminum powder, but can only bring about a simple superposition of corresponding effects. It can be seen that the combination of modified carbon nanotubes and aluminum powder is irreplaceable and can bring about a significant improvement in weather resistance.
[0069] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A fluorocarbon anticorrosive coating, characterized in that: It comprises component A and component B which are stored separately and mixed when used, and the component A comprises the following raw materials in parts by weight: 35-56 parts of fluorocarbon modified hydroxy acrylic resin; 10-15 parts water; Graphene powder 0.1-0.5 parts; Pigment 15-25 parts; 1-2 parts of fluorinated surfactant; The B component comprises the following raw materials in parts by weight: 10-12 parts of melamine compounds; The fluorocarbon-modified hydroxy acrylic resin is prepared by the following steps: Add ethylene glycol butyl ether into a reaction container, add an initiator and a monomer mixture dropwise after heating, keep warm and stir to react after the addition is completed, and add deionized water and a neutralizer to obtain a fluorocarbon-modified hydroxy acrylic resin; The monomer mixture is composed of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic acid monomer and methacrylic acid monomer hydroxyethyl ester monomer in a weight ratio of (1-2): 1: (2-5): (3-6).
2. The fluorocarbon anticorrosive coating according to claim 1, characterized in that: The monomer mixture is composed of butyl acrylate monomer, methacrylic acid monomer, fluorine-containing acrylic acid monomer and hydroxyethyl methacrylate monomer in a weight ratio of 1.5: 1:3:
5.
3. The fluorocarbon anticorrosive coating according to claim 1, characterized in that: The fluorine-containing acrylic monomer is one or a combination of hexafluorobutyl acrylate, trifluoroethyl methacrylate, perfluorohexylethyl acrylate, dodecafluoroheptyl methacrylate and perfluorooctylethyl methacrylate.
4. The fluorocarbon anticorrosive coating according to claim 1, characterized in that: The raw materials of the A component are further added with 1-3 parts by weight of a functional additive, wherein the functional additive is composed of modified carbon nanotubes and aluminum powder in a weight ratio of (5-9):1, and the modified carbon nanotubes are prepared by the following steps: The carbon nanotube raw material is added into a mixed acid solution of nitric acid and sulfuric acid, and ultrasonically treated at 40-50° C. for 6-8 hours, then cooled and allowed to stand for a period of time, diluted, filtered and washed with water to neutralize, and then vacuum dried to obtain.
5. The fluorocarbon anticorrosive coating according to claim 4, characterized in that: The functional additive is composed of modified carbon nanotubes and aluminum powder in a weight ratio of 7:
1.
6. The fluorocarbon anticorrosive coating according to claim 4, characterized in that: The carbon nanotube raw material is a multi-walled carbon nanotube with a diameter of 10-20 nm and a length of 1-10 μm; the particle size of the aluminum powder is 25-35 μm.
7. The fluorocarbon anticorrosive coating according to claim 4, characterized in that: The nitric acid is a nitric acid solution with a mass fraction of 70%, the sulfuric acid is concentrated sulfuric acid with a mass fraction of 98%, and the volume mixing ratio of the nitric acid to the sulfuric acid is 1:(3-5).
8. The fluorocarbon anticorrosive coating according to claim 1, characterized in that: The fluorine-containing surfactant is FS-31 fluorocarbon surfactant.
9. The method for preparing the fluorocarbon anticorrosive coating according to claim 1, characterized in that: The following steps are involved: (1) preparing raw materials including fluorocarbon-modified hydroxy acrylic resin, water, graphene powder, pigment, fluorinated surfactant and melamine compound according to the proportion; (2) After mixing the water and the fluorinated surfactant in step (1), add the graphene powder and the pigment, stir and mix, then grind, and then add the fluorocarbon modified hydroxy acrylic resin, stir and mix to obtain component A; and the melamine compound is component B; (3) When in use, stir and mix component A and component B to obtain a fluorocarbon anti-corrosion coating.
10. The method for preparing the fluorocarbon anticorrosive coating according to claim 9, characterized in that: Step (2) is specifically configured as follows: after mixing the water and the fluorine-containing surfactant in step (1), graphene powder and pigment are added, stirred and mixed, and then ground to a particle size of 5-40 μm, and then fluorocarbon-modified hydroxy acrylic resin is added, stirred and mixed to obtain component A; and the melamine compound is component B.